Recent Patents on Anammox Process - Li, Anhua; Sun, Guoping; Xu, Meiying (Recent Patents on Engineering, 2008)
Anaerobic ammonium oxidation process with nitrite to N2 (anammox) has become a main focus and been widely introduced as a cost-effective biological nitrogen removal way in wastewater treatment. This paper reviews various patents which were well developed to achieve this process, such as SHARON-Anammox, CANON, and OLAND. To deal with the long start-up period problem of anammox process, the methods for collecting bacterial cell and regulating the feed rate are discussed. In order to avoid inhibition of substance and pH, some improvement methods, such as pH adjustment, adding back flow denitrification vessel and simultaneously shortcut denitrification and anammox process are also described. The list of patents reviewed is not extensive,but it shows the extent of the subjects covered patents in this area during recent years. Additionally, the current status regarding application and the future developments of the technologies are discussed.
Keywords: Anammox